The effects of smoking bans on self-assessed health: Evidence from Germany - Daniel Kuehnle; Christoph Wunder (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The 16 German federal states introduced smoking bans on different dates during 2007 and 2008. These bans restricted smoking in enclosed public places, particularly in restaurants and bars. This study examines the effects of smoking bans on self-assessed health. Using data from the Socio-Economic Panel (SOEP), difference-in-differences estimations provide evidence for health improvements for the population at large. Health benefits from the secondhand smokefree environment are equivalent to an increase in household income of approximately 30%. Further subgroup analyses show that health improvements are largest among young non-smokers (below 30 years) whereas smokers report no or even adverse health effects in response to bans. Exploiting differences in the dates of introduction and enforcement, we find no evidence that the effects of bans depend on enforcement measures.
Keywords: D04; C23; I10; 330; smoking bans; self-assessed health; difference-in-differences